2006
DOI: 10.1007/s11547-006-0048-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of magnetic resonance in characterising extrahepatic cholangiocarcinomas

Abstract: MR almost always identified the cause of stenosis and suggested its neoplastic nature if it exhibited a mass-like appearance (extraductal or growing into the choledochus). On the other hand, lesions with parietal thickening, particularly if smaller than 1 cm, require endoscopic cytology or histology because of the high risk of unnecessary procedures for benign lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The T2-weighted images and the dynamic contrast-enhanced T1-weighted MR image can be helpful for detecting and characterizing the tumor (30). Contrast-enhanced MR imaging is also useful in differentiating between benign and malignant bile duct strictures (31,32). MR cholangiopancreatography is helpful in the evaluation of a periductal infiltrating or intraductal growth type tumor (33,34).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…The T2-weighted images and the dynamic contrast-enhanced T1-weighted MR image can be helpful for detecting and characterizing the tumor (30). Contrast-enhanced MR imaging is also useful in differentiating between benign and malignant bile duct strictures (31,32). MR cholangiopancreatography is helpful in the evaluation of a periductal infiltrating or intraductal growth type tumor (33,34).…”
Section: Imaging Techniquesmentioning
confidence: 99%
“…Magnetic resonance cholangiopancreatography (MRCP) is another noninvasive test with a higher sensitivity (80–90%) and specificity (88–100%) compared with transabdominal ultrasound (sensitivity <50%) for choledocholithiasis 4,5 . Although noninvasive, obtaining a timely MRCP can be a challenge and lead to delays in definitive treatment.…”
Section: Diagnosismentioning
confidence: 99%
“…Magnetic resonance cholangiopancreatography (MRCP) is another noninvasive test with a higher sensitivity (80-90%) and specificity (88-100%) compared with transabdominal ultrasound (sensitivity <50%) for choledocholithiasis. 4,5 Although noninvasive, obtaining a timely MRCP can be a challenge and lead to delays in definitive treatment. In addition, it is important to recognize that MRCP may not reveal smaller stones (<6 mm) and those in the periampullary region and provides no therapeutic capability.…”
Section: Imagingmentioning
confidence: 99%
“…A meta‐analysis showed that the sensitivity ranged from 0.32 to 1.00 with a summary sensitivity of 0.73, putting patients at risk of not receiving correct treatments if no further investigations are done 5 . On the other hand, MRCP is highly sensitive and highly specific, and similar to transabdominal US, is noninvasive, but it is more expensive and is thus reserved for certain cases 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…5 On the other hand, MRCP is highly sensitive and highly specific, and similar to transabdominal US, is noninvasive, but it is more expensive and is thus reserved for certain cases. 6,7 To the best of our knowledge, research comparing between transabdominal US and MRCP specifically for choledocholithiasis is not extensive. 8 The aim of our study is to compare the diagnostic accuracy of transabdominal US with MRCP as the gold standard in the diagnosis of choledocholithiasis in context of laboratory blood test values.…”
mentioning
confidence: 99%